Boosting Output Power of Multiwavelength Fiber Laser with Lyot Filter utilizing Hybrid Amplifier - Sulaiman A.H.; Latif H.A.A.; Abdullah F.; Ismail A.; Jamaludin M.Z.; Yusoff N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fiber lasers; Photonics; Semiconductor optical amplifiers; Extinction ratios; Hybrid amplifier; Lasing lines; Lyot filters; Multi wavelength fiber laser; Multiwavelength lasing; Output peak power; Output power; Erbium doped fiber amplifiers